PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI CILLO COFFEE - Ranata Silvia; Rully Arifiansyah (LP2M Universitas Bina Bangsa, 2023)
This research was to assess the correlation between product quality, perceived price, and service quality in relation to customer satisfaction at Cillo Coffee. The participants in the survey were individuals who visited Cillo Coffee. A sample of 100 respondents was randomly selected for the study. Multiple regression analysis using SPSS 25 was employed as the analytical method. The data collection process involved the utilization of questionnaires, which were assessed for validity and reliability. The findings of the study indicate that product quality (X1), price perception (X2), and service quality (X3) exhibit a positive and significant influence on customer satisfaction (Y).